Pulmonary Embolism Following Lung Transplantation: Prevention and Management - Mohammadi, Daniel; Keshavamurthy, Suresh (International Journal of Angiology, 2024)
Thromboembolic events are the third leading cardiovascular diagnosis following stroke and myocardial infarction. In the United States, 300,000 to 600,000 people per year are diagnosed with venous thromboembolism, either deep venous thrombosis or pulmonary embolism (PE). Of those patients, thousands die from PE despite heightened vigilance and improved therapies. Lung transplant recipients are at increased risk of developing PE due to multiple risk factors unique to this population. Additionally, the transplant recipients are more susceptible to morbid complications from PE. As a result, prevention, timely recognition, and intervention of PE in the lung transplant population are of the utmost importance.
Keywords: anticoagulation; deep vein thrombosis; embolectomy; thrombolysis; transplant; thrombectomy; risk factors